Kredit macet,BTPN Syariah ANALISIS FAKTOR-FAKTOR PENYEBAB KREDIT MACET PADA TEPAT SHARIA FINANCING PT BTPN SYARIAH DI SUMATERA BARAT - sudarman p.n laia; Silvia Rosita; Fanny Oktivia Denovis (AKTUARIA, 2026)
Abstract Non-performing loans or problem loans are loans that experience repayment difficulties due to intentional or unintentional factors beyond the debtor's control. One of the factors causing non-performing loans is the debtor's business bankruptcy, making it impossible for the debtor to repay the loan used as business capital. The purpose of this study is to analyze the factors of non-performing loans in Tepat Sharia Financing at PT. BTPN Syariah Sumatera Barat. This study uses quantitative data analysis, collecting relevant data related to the problem and research objective. Among the four factors in this study, the variable of customer's economic condition (X3) has the greatest influence on the level of non-performing loans at PT BTPN Syariah Tbk. Keywords: non-performing loans, multiple linear regression, BTPN Syariah"